PAP effect of resistance and overspeed running on kinematics and sprint performance - van den Tillaar, R. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to examine if there is a post activation potentiation (PAP) effect of resistance and overspeed sprinting upon kinematics and performance of regular 20m sprints. Fifteen female team handball players performed three training protocols: seven normal 20m sprints, or seven sprints alternating between normal and either resistance or overspeed sprints in a session. The main finding was that only resistance runs had a PAP effect on the first normal 20m sprint. However, this was only the case after one resistance run. Using several resistance runs did not have any positive effect upon the normal runs, but causes probably fatigue as shown in the increased contact times and decreased vertical stiffness, step length and rate. Overspeed running did not cause any changes to the normal runs.